Gold Nanoparticles - Synthesis and Applications in Cancer Management - M. Joseph, Manu; T. Sreelekha, Thankappan (Recent Patents on Materials Science, 2014)
Gold nanoparticles (AuNPs) are one of the most widely studied nanomaterials in the last decade, and are emerging as promising agents in cancer management. Gold nanostructures in varying size and shape, such as rods, triangles, hexagons, octagons, cubes, nanowires, nanospheres, etc. could be synthesized using various well-established physical and chemical techniques. Synthesis of AuNPs, using green chemistry approaches that utilize various materials of biological origin, such as proteins, polysaccharides, microorganisms, plant and cell extracts, have received increasing attention. AuNPs have numerous physical assets that make them appealing for applications in cancer management, including imaging, drug delivery, photothermal therapy and many more. Considering the widespread impact of AuNPs in cancer, an increasingly large number of patents have been awarded for the synthesis and medical applications of AuNPs. Owing to the importance of AuNPs in cancer management, the present review focuses on their modes of synthesis and widespread applications in cancer management, with special reference to recent patents.
Keywords: gold nanoparticles